PERANCANGAN SISTEM INFORMASI RENCANA ANGGARAN BIAYA (RAB) RUMAH SEDERHANA BERBASIS WEB - Ilham Perdana; Miral Akbar; Rekha Wulandari Putri Yuda; Helga Yermadona; Elfani Bastian (Ensiklopedia Research and Community Service Review, 2023)
The purpose of this study is to create and implement an effective program to facilitate users or the public in making and compiling budget estimates for building houses, namely by designing an application for calculating the Budget Plan (RAB) by designing using use case diagrams, creating a system with the design that has been made and implement the system that has been made and perform system testing. In collecting data, researchers used the method of observation, interviews and literature study. Meanwhile, the researcher also uses a common analytical method in the computer field, namely the System Development Life Cycle (SDLC). SDLC is an evolutionary process followed in implementing a computer-based information system or subsystem. The design of this information system uses a web programming language, namely PHP, and the database used is MySQL. This research produces an application for calculating the Budget Plan that helps users or the public to make it easier to prepare budget estimates for house construction from the initial stage to the completion of the construction.Keywords: Design, Information System, RAB Calculation, Simple house, MySQL Database.